Medication Adherence, Glycemic Control and Quality of Life in Patients with Type 2 Diabetes Mellitus: a cross-sectional study - Eliza, Delila; Syafhan, Nadia Farhanah; Andrajati, Retnosari; Fitriani, Sri Wulandah (Fakultas Farmasi Universitas Andalas, 2023)
Medication adherence is important in controlling blood sugar levels (HbA1c) in patients with Diabetes Mellitus (DM). Studies on the relationship between medication adherence and blood sugar control on the quality of life (QoL) in Type 2 DM patients are limited in Indonesia. This study aims to assess the relation between medication adherence with blood sugar control and the quality of life of Type 2 DM patients. This study used a cross-sectional design conducted at Universitas Indonesia Hospital. It used Medication Adherence questionnaires and EuroQoL 5D-5L questionnaires to assess patientsâ€™ medication adherence and quality of life. This study involved a total of 74 Type 2 DM patients with an average age of 57 Â± 10.74 years. Medication adherence with good blood sugar control (HbA1c <7%) showed a significant relationship (p-value <0.05) with COR values of 3.74 (1.21 - 11.6) compared to non-adherent patients. But not on the QoL Index and VAS (Visual Analog Scale) values, where the value is lower in patients with high adherence and good blood sugar control. Factor asscociated with blood sugar controlled were comorbidites and medication adhrence while factor that associated with quality of life were comorbidities, ages, education and employment status